To BYOD or not to BYOD: factors affecting academic acceptance of student mobile devices in the classroom - Christopher Graham Mckercher Gillies (Association for Learning Technology, 2016)
This article reports on factors affecting local academic acceptance of bring your own devices (BYOD). A review of the literature revealed a paucity of studies that have explored the complex factors that affect academic use and intention to use mobile devices in the classroom, with even less exploring truly ubiquitous and varied personal devices as opposed to supplied institutional or research study sets.A detailed qualitative investigation with 14 academics was undertaken, drawing upon and aiming to compliment mature acceptance research. Firstly by employing a focus group to identify initial psychological factors and the relevance of acceptance theories to the local context. Then, secondly by using in-depth semi-structured interviews, shaped by acceptance categories, to identify a breadth of psychological factors affecting faculty use and intention to use BYOD.This small-scale study found clear distinctions in local academic perceptions of BYOD compared with faculty devices and reported a range of factors that appeared to distinctly affect local academic acceptance of BYOD.